Effect of the electrode arrangements in a tube bank on the characteristic of electrohydrodynamic heat transfer enhancement: Low reynolds number - Kasayapanand N. (2014)
Enhancement in heat transfer using the electrohydrodynamic (EHD) technique is numerically examined in laminar forced convection across a tube bank with six different wire electrode arrangements. The electric field is generated by the wire electrodes charged with high DC voltages ranging from 7.5 to 17.5 kV. The Reynolds number corresponding to the flow considered is between 100 and 1,500. The numerical modeling of the laminar forced convection includes the interactions among the electric field, the flow field, and the temperature field. It is found that the heat transfer is significantly enhanced by the EHD at a low Reynolds number, and the short distance between the wire electrodes and the tube surface from which different electrode arrangements are reported for aligned and staggered tube configurations. The value Nu/Nu0 of an aligned configuration increases from row to row and appears to be similar with that of a staggered configuration.